DETEKSI SKOLIOSIS DAN PELATIHAN SENAM POSTURAL BAGI REMAJA PUTRI DI MANADO - Lestari, Utami Sasmita; Angmalisang, Elvin Clara; Wijaya, Nur Anindhita Kurniawaty (Universitas Mataram, 2025)
Scoliosis is a fairly common spinal disorder found in adolescents, particularly female adolescents, with a global prevalence of 0.47–5.2%. In Indonesia, a survey in Surabaya showed a prevalence of 2.93% among school-aged children. This condition, if left undetected, can lead to postural problems, back pain, and even respiratory issues. This community service program aims to conduct early detection of scoliosis and provide good posture exercise training for teenage girls in Manado. The methods used include visual examination, Adam's Forward Bend Test, and measurement with a scoliometer to detect the presence of spinal curvature. Next, a good posture exercise training was conducted, consisting of stretching movements, core muscle strengthening, and posture correction in sitting, standing, and walking positions. The activities were also evaluated using knowledge and skills questionnaires administered before and after the intervention. The activity was attended by 35 female students, and the examination results showed that most had normal posture, but 8 students showed indications of mild scoliosis. The questionnaire evaluation results indicated an increase in participants' knowledge and skills: the average knowledge score increased from 65% (pre-test) to 88% (post-test), while practical gymnastics movement skills increased from 62% to 85%. The participants' response was very positive, as evidenced by their enthusiasm in participating in both the examination and training. Discussions with teachers and students confirmed a commitment to practicing gymnastics at least twice a week. The combination of early detection and postural gymnastics training has proven effective as a preventive measure to prevent the development of scoliosis in adolescent girls. This program not only raises awareness but also strengthens adolescents' knowledge and skills in maintaining bone health.